Feeding functional oils and/or monensin for growing cattle grazing on tropical pastures - Chase Lloret, Miguel Angel (2024)
There are few studies that have tested the use of functional oils for growing zebu cattle kept on tropical pastures. Therefore, we aimed to study the response of average daily gain (ADG) and dry matter intake (DMI) of bulls to the use of a blend of cashew and castor functional oils, compared to sodium monensin, in an alternating grazing system of Urochloa brizantha, cv Marandu at the end of the summer and during the autumn. One hundred and sixty Nellore bulls, aged 15 to 17 months, were used and allocated to 8 blocks based on initial body weight (IBW: 264 ± 18.5 kg) for a period of 112 days. The experimental design was a randomized complete block design. For each block, 4 modules were assigned, each containing 2 paddocks of 1 hectare. These paddocks included a covered feeding area and free access to a water trough. Each block consisted of 4 experimental units (EU) of 5 animals each. Each EU occupied one module at a time, rotating to a new module every 28 days. This rotation ensured that no EU returned to the same module, and all EUs within a block experienced all modules. To adjust the leaf blade supply for all treatments, put-and-take bulls were added to the paddocks along with the experimental bulls, when necessary. The following four treatments were randomly assigned within each block: (1) CONT: supplementation of 0.3% of body weight (BW) of DDGS with a mineral mix without additives, (2) FO: 0.3% of BW (DM) of DDGS with a mineral mix and 2290 mg/kg of a functional oil blend (Essential®), (3) SM: 0.3% of BW (DM) of DDGS with a mineral mix and 195 mg/kg of sodium monensin (Rumensin®), (4) SMFO: 0.3% of BW (DM) of DDGS with a mineral mix, 2290 mg/kg of functional oil blend, and 195 mg/kg of monensin. At the beginning and end of the experiment, fasting weights were measured, while non-fasting weights were measured every 28 days to adjust the amount of supplement provided during the experimental period. The SMFO treatment showed a trend towards a 6.6% increase in ADG compared to the control treatment (1.034 vs. 0.970 kg; P = 0.08). There were no significant differences in ADG between the CONT, FO, and SM treatments (P>0.05), nor were there differences between the FO, SM, and SMFO treatments (P>0.05). There were no differences in final body weight (BW) or supplement intake as a percentage of BW per day among all treatments. In this study, the combination of a functional oil blend and monensin tended to improve the performance of Nellore bulls grazing tropical pastures. However, since there was a minimal difference in average daily gain (ADG) favoring the SMFO treatment (4 g/day) compared to the SM treatment, most of the benefit seems to be attributable to monensin.